Transitional justice and the prevention of torture - McGregor, Lorna (International journal of transitional justice, 2013)
In the 20 or so years since transitional justice first emerged as a field of practice, its objectives and the contexts in which it is applied have expanded greatly. However, its dual role of acknowledging the commission of past violence and human rights violations and seeking to prevent their recurrence remains central. Recent scholarship has begun to explore the impact of transitional justice in practice and also to critique its purported narrow focus on civil and political rights. Recommendations have emerged that transitional justice should address a broader range of violations, such as violations of economic, social and cultural rights, on the basis that this would more appropriately acknowledge the full ambit of past violence and also provide a stronger basis for preventing a return to the violence of the past. Through the case study of torture, this article suggests that before expanding, stock should be taken of transitional justice’s current contribution to prevention. It suggests that while transitional justice has generally prioritized certain types of torture, it has not taken a preventative approach by failing to identify and analyse the full extent of the practice and the way in which it supports institutional structures. The article assesses the extent to which transitional justice can overcome these deficiencies and proposes a possible framework for doing so.